PROCEDURE IN LITIGATION FOR PROTECTION AGAINST ILLEGAL TERMINATION OF EMPLOYMENT - Sanda Corac,; Antić, Aleksandar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
In situations where the fundamental human right to work is threatened by illegal termination of employment, i.e., if the termination of employment occurs contrary to the provisions of the Labor Law or another special law, the employee achieves protection through the court in a procedure which is regulated by the Civil Procedure Law.In the paper the authors deal with the peculiarities of the litigation procedure for protection against illegal termination of employment, but also with the normative solutions and legal consequences of illegal termination of employment that occur for the employer.
Keywords: illegal termination of employment, procedure in litigation from employment relations, consequences of illegal termination of employment, court practice